ACHIEVEMENTS AND CONSTRAINTS OF PEDIATRIC ANESTHESIOLOGY AND INTENSIVE CARE - A. U. Lekmanov (Вестник анестезиологии и реаниматологии, 2019)
The article describes the achievements of pediatric anesthesiology and intensive care in recent years. The author focuses on the humanization of critical medicine in children, effects of anesthesia on the developing brain, pain management in children, and also examines problems of respiratory support, diagnosis and intensive therapy of sepsis in children and newborns, nutritional support in critically ill children.